Genome-wide identification, evolution and expression analysis of bone morphogenetic protein (BMP) gene family in chinese soft-shell turtle (Pelodiscus sinensis) - Lei, Luo; Zhu, Junxian; Chen, Chen; Wang, Yongchang; Wu, Congcong; Qi, Ming; Wang, Yakun; Liu, Xiaoli; Hong, Xiaoyou; Yu, Lingyun; Chen, Haigang; Wei, Chengqing; et al. (Frontiers in Genetics, 2023)
Bone morphogenetic proteins (BMPs) play a crucial role in bone formation and differentiation. Recent studies suggest they may be involved in the sex differentiation of Pelodiscus sinensis, yet information about BMPs is lacking. Here, we analyzed the phylogeny, chromosomal localization, gene structures, protein structures, transcription factors and dimorphic expression of BMP gene family members using bioinformatic methods based on genomic and transcriptomic data of P. sinensis. In total, 10 BMP genes were identified, which were distributed on 10 different genomic scaffolds. Phylogenetic analysis revealed that BMP genes were divided into eight subfamilies and shared similar motifs and domains. The results of the sexually dimorphic expression profile showed that Bmp2 and Bmp15l were significantly upregulated in ovaries, while Bmp7 was remarkable downregulated in testes, suggesting that it may process a potential function in the sex differentiation of P. sinensis. Collectively, our comprehensive results provide a novel insight into studying the evolution and functions of BMP genes in P. sinensis.